The Effect Of Written Corrective Feedback On Grammatical Accuracy Of Passive Voice Tenses And Unaccusative Verbs Of Pakistani Esl Undergraduates - Muhammad, Mujtaba Syed (2023)
The impetus for undertaking the current study was that the literature on written corrective feedback (WCF) is replete with studies that have examined the efficacy of WCF on passive voice tenses and unaccusative verbs (trained and untrained), despite the challenges English language learners face in the construction of these grammatical structures. Therefore, the current study was conducted to investigate the effects of WCF on the grammatical accuracy of passive voice tenses (present, past, and perfect) and unaccusative verbs (trained and untrained) of Pakistani ESL undergraduate learners. The study has three aims:1) examining whether the provision of WCF improves the grammatical accuracy of passive voice tenses; 2) examining whether the provision of WCF improves the grammatical accuracy of unaccusative verbs (trained and untrained); 3) examining which type of WCF is most effective in helping Pakistani ESL undergraduates improve the grammatical accuracy of passive voice tenses and unaccusative verbs (trained and untrained).